RANCANG BANGUN SISTEM INFORMASI PERPUSTAKAAN PADA SMA ATTAQWA 02 BABELAN BERBASIS WEBSITE - Muharrom, Muhammad (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
SMA Attaqwa 02 Babelan is a high school with its address in Babelan District, Bekasi Regency. In ongoing library activities, it is still carried out in a conventional way, which is still taking notes in books and members come directly to the library to find out information about books. Where this activity is considered to still have problems, including limited library operating hours so that students have to go to the library physically to borrow books. The book stock is limited and the current system is not informative, so that when you come to the library to borrow the book you need, the book has not been returned by the previous borrower. The purpose of this study is to analyze the system that is currently running, in order to overcome the problems faced at Attaqwa 02 Babelan High School, by designing a Library Information System Design at Attaqwa 02 Babelan High School Based on Websites. The research framework that will be carried out in solving the problems discussed is identifying, conducting information searches based on theoretical foundations, collecting data using observation and interview methods, analyzing to find solutions to the problems faced by SMA Attaqwa 02 Babelan.